Bridging the Digital Divide: Leveraging Social Media for Enhanced Corporate Learning and Digital Literacy Among Older Adults - Ochoa Siguencia, Luis (International Journal of Advanced Corporate Learning (iJAC), 2025)
This paper addresses the innovative strategies adopted by the DigIN project in order to increase digital literacy among adults aged 55 years and above using social media platforms, particularly YouTube and Spotify. The project will create an active learning community by sharing relevant educational content tailored to meet the needs of older learners. Analytics gathered data from all platforms, showing key performance indicators, including views and engagement rates and insight into demographics. Preliminary findings indicate high engagement; for example, on the YouTube channel, there were 2120 views and a total of 42.9 hours of watching time, with 42% of viewers falling into the age group 55–64. What is more, those podcasts published on Spotify were highly rated, especially among Polish speakers, thus proving great interest in digital competencies locally. Results prove that social media can be quite a useful tool for corporate learning and human resources development, with the aim of singling out the need for tailored content, taking into consideration peculiar challenges that, in general, arise while teaching older adults. The implications, therefore, for future corporate training initiatives lie in the use of social media to create learning environments that empower underserved populations and, by extension, increase their independence and overall workforce competency.